An audience focused approach to framing climate-change communication in agriculture - Wandersee, Cassie (Kansas State University, 2016)
The purpose of this study was to explore the frames and messages, issue salience, and communication preferences agricultural producers in Kansas, Oklahoma, and Texas use and accept related to climate change and the impacts of a changing climate. It was of additional interest to explore the climate-change beliefs and preferred agricultural media sources for climate and climate change information. Specific research objectives to guide the study were RO1: describe the level of issue salience agricultural producers have related to climate change; RO2: investigate frames and messages agricultural producers prefer in reference to the scientifically designated phenomena of climate change and impacts; and RO3: identify the agricultural media and information channels agricultural producers use for climate change. Based on findings in previous research, one hypothesis was developed: H1: agricultural producers in the Southern Plains Regional Climate Hub area will be located within the audience segment groups of the concerned and the cautious as identified in the Six America’s (2012) study. An Internet survey was distributed to producers in Kansas, which was open from March 3 to March 14, 2016, with 158 responses to the survey. Agenda-Setting Theory served as the basis for the study including the tenants of issue salience and framing in relation to climate change. The study found that the majority (n = 158, 64.92%) of producers believed that climate change was occurring, however, the causes were still contested. The study identified that higher levels of risk perception and education level were linked to belief in anthropogenic climate change (ACC). Primarily, the study found that loss framing was most effective in communicating the impacts of climate change. Terminology and distance framing were less important in message framing. Regional and university publications were cited most frequently by producers as sources of climate and climate-change information and overall use of agricultural media publications was linked to higher levels of belief in ACC. Users of business reports and TV had the highest mean climate-change belief; non-users had the lowest. Audience segments aligned with cautious and concerned Six America’s (2013) audience segment group, which indicated a shift towards accepting climate change among agricultural producers.
Keywords: Agenda setting theory; Issue salience; Framing; Climate-change communicationClimate change